The Sykes-Picot agreements – phase two of the partition process - Guediri, Kaoutar (السفير العربي, 2016)
Exactly a hundred years ago, in 1916, expecting the imminent collapse of the Ottoman Empire, and in order to expand their spheres of influence in the Middle East, the United Kingdom and France concluded a secret agreement with the assent of Tsarist Russia.